2021
DOI: 10.3390/foods10102300
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Based Methodologies to Extend the Shelf Life of Fresh Fish—A Review

Abstract: Due to its characteristics, fresh fish is a highly perishable food with a very short shelf-life under refrigeration. Several methods have been introduced to slow down its deterioration, such as by means of oxygen depletion of the food package (vacuum packaging), or by changing the natural atmosphere that is in contact with the fresh fish (modified atmosphere packaging), or by the use of chemicals generally recognized as safe: such compounds can be directly applied (by dipping or spraying) or incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 114 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…It was therefore supposed that maintaining the pH of sea bass under low levels (<pH 7.0) to inhibit the activity of MMP‐9 may be an effective strategy to reduce its quality deterioration during storage. It has been indicated that organic acids (i.e., citric, ascorbic, and lactic acids) could be used to inhibit microbial growth and/or enzymatic autolysis by reducing the pH of the environment of fish (Amaral et al., 2021; Sanjuas‐Rey et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It was therefore supposed that maintaining the pH of sea bass under low levels (<pH 7.0) to inhibit the activity of MMP‐9 may be an effective strategy to reduce its quality deterioration during storage. It has been indicated that organic acids (i.e., citric, ascorbic, and lactic acids) could be used to inhibit microbial growth and/or enzymatic autolysis by reducing the pH of the environment of fish (Amaral et al., 2021; Sanjuas‐Rey et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Icing is used to store fish at high temperatures before using the freezing method but the rate of deterioration depends upon the harvesting and handling approach. The icing technique has been used to perform different functions including maintenance of uniform low temperatures, reducing autolysis and bacterial degradation and providing gentle washing and cleaning during melting [ 49 ]. In a cooling technique, both enzymatic and non-enzymatic activities remain and continue with microbial growth.…”
Section: Preservation Technology Approaches Of Fishmentioning
confidence: 99%
“…Sheep meat is prone to microbial contamination during storage, transportation, and sales, leading to spoilage and the loss of its edibility and commercial value. Modified atmosphere packaging technology can partially compensate for the limitations of vacuum packaging and further delay microbial-induced spoilage [3]. Traditional detection methods often require experienced professionals to perform inspection, which is time-consuming and destructive to the samples, thus reducing detection efficiency and no longer meeting the current industrial development requirements [4,5].…”
Section: Introductionmentioning
confidence: 99%